Representações da modernidade fluminense em textos literários de Machado de Assis e Lima Barreto - Rodrigues, Davidson de Oliveira (Universidade Federal de São Carlos, 2017)
The present work analyzes the representations of the city Rio de Janeiro in literary texts of Machado de Assis and Lima Barreto. This study determines the type of evaluation that these writers made of the modern aspects of the capital of Rio de Janeiro. The chronological framework is between the last two decades of the nineteenth century and the first years of the twentieth century. The initial assumption of the research considered these writers as skilled observers of the social environment in which they lived. Another presupposition is that the nineteenth-century literature constitutes an important collection of visions about the urban (both in Europe and in Brazil). Thus, Machado de Assis and Lima Barreto are analysts of urban life in Rio. The basic unit of research analysis is the category of representation. Its application is through the methodology of selection of texts from the set of complete works for further analysis. The detailed reading of fragments is done in order to identify images and allusions concerning the urban universe. The analysis carried out demonstrates the existence of representations of sociability and urban sensibility in the literature of the mentioned writers. The novels “Esau e Jacó” and “Triste fim de Policarpo Quaresma” bear a set of representations about Rio de Janeiro that describe the way of life of a capital during the period that was designated to call like “Belle Époque”. The city is represented as the political and cultural center of the country. This work disputes the notion that the mentions to Rio de Janeiro in the literature of Machado are mere scenographies. The detailed study of the tales “Uns braços”, “Missa do galo”, “A cartomante”, “A causa secreta” reveals the kind of understanding that Machado de Assis developed on indeterminacy in everyday life: Rio is presented as a complex city In which the characters often encounter several lines resulting from the flow of everyday events. In Barreto's literature, the appearance / essence tension and social exclusion explain the representations of the city as a permanent estrangement from European to African culture. The study of the tales “Um e outro”, “O homem que sabia javanês”, “Cló”, “O filho de Gabriela” reveals the kind of understanding that Lima Barreto developed about the insulation of modern life: Rio is presented as a city empty of a common cultural heritage. The general considerations of this work establish that the literary images of the city of Rio de Janeiro make up a system of representations whose effect is to bring Rio de Janeiro's capital closer to European cities. Westernizing, modernizing, and liberal traits were emphasized to cover up the archaic, rural, and colonial dimensions of the country. In this way, the valorization of “europeidade” allowed the intellectual and dominant groups to identify with the European way of life. Machado de Assis and Lima Barreto, however, deconstructed these imagery through ironic and critical expressions, exposing the contradictions of urban life in Rio. Thus, the representations of Rio de Janeiro in the literature of both tended to show indetermination and estrangement as typical features of modern life in Rio.
Keywords: Machado de Assis; Lima Barreto; Visões do urbano; Representações do Rio de Janeiro; Visions of the urban; Representations of Rio de Janeiro; CIENCIAS HUMANAS::SOCIOLOGIA